Control of dual hydraulic free piston engine. (17th March 2006) - Tikkanen, S.; Vilenius, M.
A free piston engine, FPE, combines a combustion engine and a hydraulic pump in one compact component. The only moving part in the hydraulic FPE is the piston assembly containing combustion piston(s), piston rod and pump piston. The piston assembly moves during operation linearly back and forth between left and right extremes by means of the fuel energy. Simultaneously, the pump produces directly fluid flow. The simplicity of mechanical design sets high requirements for the control system. In this paper the control principle of one FPE design is introduced and analysed.